Assessment of efficacy of a new scheme of movalis administration in osteoarthritis and rheumatoid arthritis (data of a TOC ø "1-5" \h \z Russian multicentr study) - E S Tsvetkova (Научно-практическая ревматология, 2005)
Objective. To assess efficacy and safety of "stepped" therapy with movalis (consecutive parenteral administration during 3 days and oral during 20 days 15 mg/day) for exacerbation of chronic pain in rheumatic diseases. Methods 262 pts with raheumatoid arthritis (RA) and 384 pts with osteoarthritis (OA) in 22 cities of Russia were included. Quantitative assessment (using 10-point scale) of clinical parameters (pain at rest and at movement, severity of functional disturbances and local inflammation) at different phases of therapy was performed. Frequency and character of adverse events in pts having risk factors of adverse events were analyzed. Results. Intramuscular movalis administration provided fast analgesic and anti-inflammatory effects which increased during the second phase (oral) of treatment. Despite of presence risk factors adverse events were rare and mild. Conclusion. These data show high efficacy and safety of movalis in RA and OA.